2019
DOI: 10.1111/jvh.13217
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and burden of HBV co‐infection among people living with HIV: A global systematic review and meta‐analysis

Abstract: Globally, in 2017 35 million people were living with HIV (PLHIV) and 257 million had chronic HBV infection (HBsAg positive). The extent of HIV‐HBsAg co‐infection is unknown. We undertook a systematic review to estimate the global burden of HBsAg co‐infection in PLHIV. We searched MEDLINE, Embase and other databases for published studies (2002‐2018) measuring prevalence of HBsAg among PLHIV. The review was registered with PROSPERO (#CRD42019123388). Populations were categorized by HIV‐exposure category. The glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
105
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(113 citation statements)
references
References 231 publications
3
105
1
4
Order By: Relevance
“…A recent meta-analysis noted a co-seroprevalence of 4.4% for the Southern African region. 2 Earlier studies found that patients with HBV coinfection are at a higher risk to develop liver fibrosis and cirrhosis. 4,13 Although the diagnostic accuracy of APRI is inferior to an ultrasound-guided assessment of liver elasticity (fibroscan) or liver biopsy, the WHO recommends APRI for the clinical management of HBV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent meta-analysis noted a co-seroprevalence of 4.4% for the Southern African region. 2 Earlier studies found that patients with HBV coinfection are at a higher risk to develop liver fibrosis and cirrhosis. 4,13 Although the diagnostic accuracy of APRI is inferior to an ultrasound-guided assessment of liver elasticity (fibroscan) or liver biopsy, the WHO recommends APRI for the clinical management of HBV.…”
Section: Discussionmentioning
confidence: 99%
“…1 Persons living with the human immunodeficiency virus (HIV) are a key population most affected by HBV and HCV infection. 2,3 Coinfection with HIV has been identified as an additional factor for fibrosis progression and liver carcinogenesis. 4 The estimated global prevalence of HIV/HBV coinfection is 7.6%, leading to 2.7 million individuals simultaneously carrying HIV and HBV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBV incidence has also been shown to be moderately high in HBV-endemic settings among PLWH with relatively preserved CD4 cell counts [44]. HBV burden is also higher among marginalized populations such as those who inject drugs or are imprisoned, who are also at greater risk of HIV [2,45]. Unfortunately, despite recommendations to immunize all susceptible persons with HIV against hepatitis B, one study conducted by the US Centers for Disease Control of over 18,000 patients in HIV care from 2009 to 2012 found that 44.2% had no documentation of HBV vaccination, immunity or infection in the medical record [46•].…”
Section: Hbv Prevention With the Goal Of Eliminationmentioning
confidence: 99%
“…Despite the development of a safe and efficacious hepatitis B vaccine in 1982 [1], the hepatitis B virus (HBV) remains a public health burden in sub-Saharan Africa with a reported prevalence of about 6% [2,3]. While mortality in sub-Saharan Africa from the World Health Organization (WHO)-targeted infectious diseases (i.e.…”
Section: Introductionmentioning
confidence: 99%